Predictors of Seatbelt Use Among Saudi Adults: Results From the National Biobank Project - Alghnam, Suliman; Alyabsi, Mesnad; Aburas, Alhanouf; Alqahtani, Taif; Bajowaiber, Miasem; Alghamdi, Ali; Alqunaibet, Ada (Frontiers in Public Health, 2020)
Abstract Introduction: Road traffic crashes (RTCs) are a leading cause of death and disabilities, posing a significant burden on healthcare and the economy of Saudi Arabia. Around 20% of all hospital beds are occupied by victims of RTCs, reaching approximately 80% of trauma deaths occurring in these facilities. Using a seatbelt is an effective method to reducing traffic deaths and minimizing the extent of associated injuries. Currently, little is known on the prevalence and predictors of seatbelt use in the Kingdom. More studies are needed to inform upon the trend of seatbelt use and study the relationship between individual factors and compliance with the seatbelt use law. The present study aims to examine the prevalence and predictors of seatbelt use utilizing the National Saudi Biobank dataset. Materials and Methods: This is a cross-sectional study using an in-person survey from the Saudi National Biobank. Participants were adults affiliated with the Ministry of National Guard Health Affairs in Riyadh between 2017-2019. Chi-square and Wald tests were used to assess the association between respondents’ characteristics and seatbelt use. In addition, logistic regression models were constructed to assess the univariate and multivariate association between seatbelt use and potential predictors. All statistical tests were two-sided, and findings were considered significant at P< 0.05. Results: A total of 5,790 adults participated in the survey. The majority of the participants (52.44%) were between 18-25 years old, half were males, and 58.80% were single. About 42.83% of the participants reported consistent seatbelt use as drivers or passengers. In the multivariable analysis, females were 86% less likely to wear seatbelts than males (OR=0.136, 95%CI=0.107-0.173). Individuals who rated their mental health as “weak” were 26% less likely to wear seatbelts than those with a reported “excellent” mental health status. Conclusion: Seatbelt use remains low in the country and substantially lower than in developed countries. Young adults, females, and individuals with reported suboptimal mental health were less likely to fasten their seatbelts. These findings are valuable for public health programs to target specific groups and raise awareness about the need to increase seatbelt compliance and reduce traffic injuries.